HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN DALAM PEMBERIAN IMUNISASI PENTABIO PADA BAYI DI WILAYAH KERJA PUSKESMAS JAILOLO KABUPATEN KABUPATEN HALMAHERA BARAT - Samsudin, Fahima; Purwati, Anik (NHM PRESS, 2024)
Background: Optimal breastfeeding is important. Earlybreastfeeding initiation (IMD) is one of the factors thatdetermine the success of exclusive breastfeeding for 6months. The benefits of IMD include reducing the risk ofmaternal mortality, increasing the chances of successfulexclusive breastfeeding for 6 months, preventingneonatal deaths, and increasing closeness and affectionbetween mother and child (Ekaristi et al., 2017). Thepurpose of this study was to determine the relationshipbetween early breastfeeding initiation (IMD) andexclusive breastfeeding in West Halmahera district. Earlybreastfeeding (IMD) must be done for the success ofexclusive breastfeeding and for the health of mothersand babies. Objective: This study aimed to determinethe relationship between the implementation of earlybreastfeeding initiation and exclusive breastfeeding withexclusive breastfeeding in children aged 0-10 months atthe Jailolo Health Center, West Halmahera Regency.Method: This type of research used analytic researchwith a case control study design. Sampling was done bypurposive sampling with a total sample of 40 mothers.This study was conducted in the Jailolo Health Centerarea, West Halmahera Regency. This data analysis usedchi square. The results showed that IMD has a significantrelationship with exclusive breastfeeding Results: Thestatistical test results obtained p value = 0.055. Thisshows that there is a relationship between the IMDvariable (Early Breastfeeding Initiation) and ExclusiveBreastfeeding (p<0.05) so that the H1 Hypothesis isaccepted that there is a relationship between EarlyBreastfeeding Initiation and exclusive breastfeeding inbabies 0-10 months in the Jailolo Health Center area,West Halmahera Regency. Conclusion: There is arelationship between early breastfeeding initiation (IMD) variable (Early Breastfeeding Initiation) and ExclusiveBreastfeeding (p<0.05) so that the H1 Hypothesis isaccepted that there is a relationship between EarlyBreastfeeding Initiation and exclusive breastfeeding inbabies 0-10 months in the Jailolo Health Center area,West Halmahera Regency. Conclusion: There is arelationship between early breastfeeding initiation (IMD)and exclusive breastfeeding in infants 0-10 months witha p value of 0.055.